The Imapact of Paracetamol on the Excretory System: A Review of Toxicity and Protective Strategies - Bante , Punam; Sethiya, Shikha; Thakare, Mangala; Dr.Varsha Dhurvey (International Journal of Scientific Research in Biological Sciences, 2025)
Paracetamol, a painkiller and antipyretic, works well for pain and fever. But its availability and perceived safety puts us at risk of accidental overdose which can cause liver damage, kidney failure, and other side effects. Paracetamol works by inhibiting COX-2 enzymes, reducing prostaglandin production, and targeting the hypothalamus to relieve pain, inflammation, and fever. But overdose can cause severe kidney damage and impairment leading to acute and chronic renal dysfunction. Studies have shown that paracetamol administration can cause nephrotoxicity characterized by histopathological changes, oxidative damage, and apoptosis. Long term and repeated intake can cause kidney dysfunction, damage, and ultrastructure defects. Fortunately, several compounds have been found to counteract paracetamol’s toxic effects including Nigella sativa, nitric oxide, alpha- lipoic acid, quercetin, curcumin, and antioxidants. These substances have been shown to reduce oxidative stress, inflammation, and kidney damage caused by paracetamol overdose. In summary, while paracetamol is widely used as an effective painkiller, its potential for overdose and toxicity requires cautious use and awareness of the risks. The identification of compounds that can counteract paracetamol’s toxic effects is a promising avenue to reduce paracetamol-induced kidney damage and safe treatment.